PENGARUH SUBSTITUSI TEPUNG TALAS TERHADAP KUALITAS KULIT KUE SUS - Rusi Cahdian; Elida Elida; Wiwik Gusnita (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
The purpose of this study was to analyze the effect of substitution of taro flour as much 25%, 50% and 75% on quality choux paste covers volume, shape, color, smell, texture and taste. The type of this research was pure experiments (true experiment) with completely randomized design method. Data tipe that is primary data sourced from 30 semi trained panelists by replying the organoleptic test format. Analyze data using ANAVA, if Fcount > Ftable then proceed with Duncan test. The results showed that there was a significant effect on quality volume, shape, color, smell, and taste, and there was no significant effect on quality texture. The best result based on organoleptic test found in X1 with substitution of taro flour as much 25%.